IDNLearn.com provides a comprehensive platform for finding accurate answers. Ask your questions and get detailed, reliable answers from our community of experienced experts.
Sagot :
To determine which of the given equations models the same quadratic relationship as [tex]\( f(x) = 2x^2 - 12x + 11 \)[/tex], we need to express [tex]\( f(x) \)[/tex] in the standard form [tex]\( a(x-h)^2 + k \)[/tex].
First, start with the given quadratic function:
[tex]\[ f(x) = 2x^2 - 12x + 11 \][/tex]
We will complete the square to rewrite this in vertex form [tex]\( a(x-h)^2 + k \)[/tex].
1. Factor out the coefficient of [tex]\( x^2 \)[/tex] from the [tex]\( x \)[/tex]-terms:
[tex]\[ f(x) = 2(x^2 - 6x) + 11 \][/tex]
2. To complete the square inside the parentheses, take the coefficient of [tex]\( x \)[/tex] (which is [tex]\(-6\)[/tex]), halve it, then square it:
[tex]\[ \left( \frac{-6}{2} \right)^2 = (-3)^2 = 9 \][/tex]
3. Add and subtract this square inside the parentheses:
[tex]\[ f(x) = 2(x^2 - 6x + 9 - 9) + 11 \][/tex]
[tex]\[ f(x) = 2((x - 3)^2 - 9) + 11 \][/tex]
4. Distribute the 2 and simplify:
[tex]\[ f(x) = 2(x - 3)^2 - 18 + 11 \][/tex]
[tex]\[ f(x) = 2(x - 3)^2 - 7 \][/tex]
So, in vertex form, the quadratic function [tex]\( f(x) = 2x^2 - 12x + 11 \)[/tex] can be expressed as:
[tex]\[ f(x) = 2(x - 3)^2 - 7 \][/tex]
Now, comparing this result with the given choices:
A. [tex]\( y = 2(x-6)^2 + 5 \)[/tex]
B. [tex]\( y = 2(x+6)^2 + 2 \)[/tex]
C. [tex]\( y = 2(x+3)^2 - 7 \)[/tex]
D. [tex]\( y = 2(x-3)^2 - 7 \)[/tex]
We observe that option D matches our transformed equation:
[tex]\[ y = 2(x - 3)^2 - 7 \][/tex]
Therefore, the correct answer is
[tex]\[ \boxed{D} \][/tex]
First, start with the given quadratic function:
[tex]\[ f(x) = 2x^2 - 12x + 11 \][/tex]
We will complete the square to rewrite this in vertex form [tex]\( a(x-h)^2 + k \)[/tex].
1. Factor out the coefficient of [tex]\( x^2 \)[/tex] from the [tex]\( x \)[/tex]-terms:
[tex]\[ f(x) = 2(x^2 - 6x) + 11 \][/tex]
2. To complete the square inside the parentheses, take the coefficient of [tex]\( x \)[/tex] (which is [tex]\(-6\)[/tex]), halve it, then square it:
[tex]\[ \left( \frac{-6}{2} \right)^2 = (-3)^2 = 9 \][/tex]
3. Add and subtract this square inside the parentheses:
[tex]\[ f(x) = 2(x^2 - 6x + 9 - 9) + 11 \][/tex]
[tex]\[ f(x) = 2((x - 3)^2 - 9) + 11 \][/tex]
4. Distribute the 2 and simplify:
[tex]\[ f(x) = 2(x - 3)^2 - 18 + 11 \][/tex]
[tex]\[ f(x) = 2(x - 3)^2 - 7 \][/tex]
So, in vertex form, the quadratic function [tex]\( f(x) = 2x^2 - 12x + 11 \)[/tex] can be expressed as:
[tex]\[ f(x) = 2(x - 3)^2 - 7 \][/tex]
Now, comparing this result with the given choices:
A. [tex]\( y = 2(x-6)^2 + 5 \)[/tex]
B. [tex]\( y = 2(x+6)^2 + 2 \)[/tex]
C. [tex]\( y = 2(x+3)^2 - 7 \)[/tex]
D. [tex]\( y = 2(x-3)^2 - 7 \)[/tex]
We observe that option D matches our transformed equation:
[tex]\[ y = 2(x - 3)^2 - 7 \][/tex]
Therefore, the correct answer is
[tex]\[ \boxed{D} \][/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Your questions deserve reliable answers. Thanks for visiting IDNLearn.com, and see you again soon for more helpful information.